2022
DOI: 10.1038/s41591-022-01872-6
|View full text |Cite
|
Sign up to set email alerts
|

City-level impact of extreme temperatures and mortality in Latin America

Abstract: Climate change and urbanization are rapidly increasing human exposure to extreme ambient temperatures, yet few studies have examined temperature and mortality in Latin America. We conducted a nonlinear, distributed-lag, longitudinal analysis of daily ambient temperatures and mortality among 326 Latin American cities between 2002 and 2015. We observed 15,431,532 deaths among ≈2.9 billion person-years of risk. The excess death fraction of total deaths was 0.67% (95% confidence interval (CI) 0.58–0.74%) for heat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 41 publications
1
44
1
2
Order By: Relevance
“…An attribution study showed that climate change increased heat-related mortality risk during the 2003 European heatwave -with the highest increase of approximately 70% occurring in central Paris 2 . Alongside the risks associated with heatwaves themselves, a recent study showed that higher ambient temperatures in Latin America increased the risk of premature death by 5.7% per 1 °C increase 3 . Another study considering data covering 43 countries and the period 1991-2018 showed that 37% of heat-related deaths in the warm seasons could be attributed to climate change 4 .…”
Section: Heating Upmentioning
confidence: 99%
“…An attribution study showed that climate change increased heat-related mortality risk during the 2003 European heatwave -with the highest increase of approximately 70% occurring in central Paris 2 . Alongside the risks associated with heatwaves themselves, a recent study showed that higher ambient temperatures in Latin America increased the risk of premature death by 5.7% per 1 °C increase 3 . Another study considering data covering 43 countries and the period 1991-2018 showed that 37% of heat-related deaths in the warm seasons could be attributed to climate change 4 .…”
Section: Heating Upmentioning
confidence: 99%
“…The intricate relationships between environmental, lifestyle and genetic factors and their respective and collective involvements in the risk development of CVD poses a colossal challenge to decreasing global burdens [2][3] . Despite difficulties in pinpointing underlying causes for exacerbating CVD, multiple studies have clearly illuminated the impact that climate and temperature, especially cold weather [4][5] and the winter season [6][7] , impose on the incidence of cardiovascular events.…”
Section: Cardiovascular Disease and Temperaturementioning
confidence: 99%
“…The frequency, intensity, and duration of extreme temperature events are expected to rise worldwide, prompting a sharp increase in population exposure to extreme temperatures in the coming decades [ 1 , 2 , 3 , 4 ]. Although several studies have documented the health risks associated with extremely cold and extremely hot temperatures, a globally comprehensive understanding of population exposure to extreme temperatures is lacking [ 5 , 6 , 7 , 8 , 9 ], and the scale of population exposure and its quantitative relationship with health risks remain unknown. This restricts our ability to identify how to distribute resources to deal with emerging health risks (reducing population-wide exposure versus increasing the resistance of vulnerable populations) [ 1 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effects of extreme temperature have been found to be heterogeneous [ 1 , 9 , 11 , 20 ]. Despite there being several studies in low-income and middle-income countries (LMICs), an increasing number of studies are reporting that low socioeconomic status (SES) is associated with stronger temperature-related mortality, because LMICs lack the human and financial resources to deal with extreme temperatures [ 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%